1973
DOI: 10.1103/physrevb.8.2906
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Interstitial in the Diamond Lattice

Abstract: Linear-combination-of-atomic-orbitals -molecular-orbitals cluster calculations using the extended Huckel theory are carried out for the interstitial carbon in the diamond lattice. The results suggest that the interstitial configuration is not the tetrahedral or hexagonal site, as has been previously assumed, but is instead an "interstitialcy" configuration, i.e. , either a split-(100) interstitial (which our results favor) or a bond-centered interstitial. The predicted minimum-energy configuration changes with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

1974
1974
2003
2003

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 104 publications
(14 citation statements)
references
References 41 publications
3
11
0
Order By: Relevance
“…Table 1 furnishes a concise description of the four models dealt with in this paper. T30, B32, and 535 have been described in connection with earlier work on carbon interstitial in diamond [13]. The H38 cluster has the hexagonal site as its center, with a total of 38 silicon atoms in all.…”
Section: Modelsmentioning
confidence: 96%
See 1 more Smart Citation
“…Table 1 furnishes a concise description of the four models dealt with in this paper. T30, B32, and 535 have been described in connection with earlier work on carbon interstitial in diamond [13]. The H38 cluster has the hexagonal site as its center, with a total of 38 silicon atoms in all.…”
Section: Modelsmentioning
confidence: 96%
“…The basic geometry and symmetry of diamond-type structures has been described in detail in a n earlier paper [13]. Table 1 furnishes a concise description of the four models dealt with in this paper.…”
Section: Modelsmentioning
confidence: 98%
“…Also experimentally it has been shown that A1+*(3s) [16] and Na(3s) [17] occupy this site. Previous EHT studies had shown that this site was not a preferred defect configuration [13]. They predicted complicated configurations such as split interstitials.…”
Section: Resultsmentioning
confidence: 97%
“…1 a. As can be seen, these 120 MO levels can be divided into two bands, a valence and a conduction band. There are more levels in the valence band than in the conduction band because the energies for all the 40 dangling orbitals on the surface of the cluster are also in this band [17]. The remaining 80 levels are divided equally between valence and conduction bands.…”
Section: Results Of Calculationsmentioning
confidence: 99%